A Unique Case of an Expanded Polytetrafluoroethylene Graft Rupture 14 Years after Abdominal Aortic Aneurysm Open Repair Managed with Placement of a Thoracic Endograft - Alexopoulou-Prounia, Loukia; Kakkos, Stavros K.; Papageorgopoulou, Chrysanthi P.; Katsanos, Konstantinos; Zampakis, Peter; Tsantrizos, Polyzois; Ntouvas, Ioannis (AORTA, 2021)
We report a unique case of expanded polytetrafluoroethylene (ePTFE) tube graft rupture that occurred 14 years after abdominal aortic aneurysm (AAA) repair. Endovascular repair with a thoracic endograft was performed. Postoperatively, an increase in the size of the existing hematoma with active extravasation occurred and was managed with iliolumbar artery embolization. Τo the best of our knowledge, rupture of ePTFE graft used for AAA repair has not been reported in the literature.
Keywords: abdominal aortic aneurysm; endovascular repair; graft rupture; iliolumbar embolization